Living With Hypochondroplasia: A Qualitative Exploration of Children's and Caregivers' Experiences, Challenges, and Unmet Needs - Oehrlein, Elisabeth M.; Pekala, Reni; Cavallaro, Stacie; Cho, Margaret; Crews, Chandler; Dauber, Andrew; Saxena, Ankita; Vandigo, Joe; Reese, Emily S. (Molecular genetics & genomic medicine, 2025)
Hypochondroplasia (HCH) is a rare genetic skeletal dysplasia characterized by short stature, disproportionate limbs, and complications such as learning differences. Currently, no treatments are approved to address HCH-related short stature, which can adversely affect quality of life. This study aimed to explore diagnostic processes, care pathways, daily life impacts, and unmet needs in HCH. Ninety-minute interviews were conducted with nine children and young adults and 25 caregivers who had physician-confirmed HCH. Participants discussed diagnostic journeys, treatment considerations, and day-to-day challenges. Following interviews, two 90-min focus groups among caregivers (n = 10) were conducted to explore themes emerging during interviews. We found that diagnostic pathways vary significantly, with signs of HCH identified in utero or during infancy or early childhood. Families described complex psychosocial burdens that include impacts on daily activities and emotional challenges due to height differences and disproportionate limb length. Additionally, many people with HCH have complications that go beyond short stature and include developmental delays, learning differences, and seizures. Families desire more support and resources related to HCH. Future efforts should focus on holistic, patient-centered strategies to better support individuals with HCH and their families.